2021
DOI: 10.1088/1361-665x/ac41ea
|View full text |Cite
|
Sign up to set email alerts
|

Frontally polymerizable shape memory polymer for 3D printing of free-standing structures

Abstract: Four-dimensional (4D) printing is used to describe three-dimensional (3D)-printed objects with properties that change over time. Shape memory polymers (SMPs) are representative materials for 4D printing technologies. The ability to print geometrically complex, free-standing forms with SMPs is crucial for successful 4D printing. In this study, an SMP capable of frontal polymerization featuring exothermic self-propagation was synthesized by adding cyclooctene to a poly(dicyclopentadiene) network, resulting in sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 55 publications
(60 reference statements)
0
15
0
Order By: Relevance
“…Future efforts to achieve large-scale FP extrusion, however, may benefit from earlier works described in this review. 32,155,160,238,364 6. Summary and Outlook 6.1 Summary: Where are We Now?…”
Section: Large-scale Fabrication and 3d-printingmentioning
confidence: 99%
See 3 more Smart Citations
“…Future efforts to achieve large-scale FP extrusion, however, may benefit from earlier works described in this review. 32,155,160,238,364 6. Summary and Outlook 6.1 Summary: Where are We Now?…”
Section: Large-scale Fabrication and 3d-printingmentioning
confidence: 99%
“…Apart from ATRP and polyurethanes, which have not been thoroughly investigated, only FROMP occurs catalytically with the use of the commercial Grubbs-type ruthenium alkylidene complexes (e.g., G1 and G2). 32,41,49,66,69,70,73,102,106,124,[145][146][147]151,152,160,162,163 Highly strained, cyclic olefins undergo living catalytic polymerization; frontally derived polymers of dicyclopentadiene (DCPD) exhibit desirable mechanical properties via extensive crosslinking during catalysis. Perhaps counterintuitively to most catalyst design principles, FROMP and polyurethane-based systems 68,72,[193][194][195] require worse catalysts to circumvent rapid background polymerization.…”
Section: Large-scale Fabrication and 3d-printingmentioning
confidence: 99%
See 2 more Smart Citations
“…Lendlein and Langer reported that SMPs may be used as self-tightening sutures for minimum invasive surgery in 2002, raising much interest for SMPs in biomedical applications. [15] Recent expansion from the traditional dual to multiple shape memory effect (M-SME) [16,17] and reversible two-way shape memory effects (2W-SMPs) [18][19][20] has greatly broadened the applications of SMPs, such as biomedical sciences, [21,22] temperature sensors, [9] actuators, [6] 3D printing, [1,23,24] flexible electronics, [11] smart textiles, [25,26] surgical materials, and aerospace devices. [27] Based on the number of fixed temporary shapes, SMPs can be divided into dual, triple, and multiple shape memory polymers.…”
Section: Introductionmentioning
confidence: 99%